PEREMPUAN PEMENANG PEMILUKADA STUDI PERSPEKTIF GENDER DAN MELURUHNYA BUDAYA PATRIARKIDI PROPINSI JAWA TIMUR - Nurul Azizah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2014)
This article discusses the winner of the election of women as a gender perspective studies and studies fading patriarchal culture in the province of East Java. The purpose of the study is; (1). Explores the political motives of candidates, kandidasi process, support election management bodies and CSOs, and the issue of gender equality in the nomination, and political context that allows the emergence of female kandidasi process. (2). Get an overview of the political profile candidates, kandidasi process, the role and support of election management bodies and the CSO, and the issue of gender equality in the nomination, and political context in the kandidasi process. (3). Interpret the presence of women in the election. The results of this study indicate that changes in the local political order decentralization followed by the application of the system of regional head election (election) directly, the more open structure of opportunity for women from various backgrounds to exist in the political space. If the existence of women in kandidasi lawmakers have increased, not the case in the election candidates are still relatively new